A Review of Content Based Image Mining System (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
In recent years, with the spread of the internet, there is a large amount of data available at it. Therefore, it becomes necessary to find fast search engines to retrieve images and documents. Image retrieval is a very significant area in digital image processing. To understand and learn more about "image retrieval system", the current study presents a review to describe the types of image retrieval techniques, explain the advantages and disadvantages of them. Moreover, this paper reviews different research studies and methodologies that applied to the area of CBIR.